Oilseed Crop Cultivation in TR71 Region and Effects Of Climate Change - İsmail Demir (Turkish Journal of Agriculture: Food Science and Technology)
This study contains the yield evaluations on oilseed crops cultivation in TR71 region, which contains Niğde Kırşehir, Aksaray, Niğde and Nevşehir provinces and is also known as Ahiler Development Agency. Effects of climate change on oilseed crops based on climate projections of the next 30 years was have been analyzed. Changes in surface temperature values and precipitation amounts for the period of 2011-2041 have been evaluated seasonally and annually with the corresponding values of 1961-1990(RF). Based on the RegCM3-ECHAM5-A2 scenario, the average temperature is expected to increase 0.2-0.6 Co until 2041. The smallest temperature change is predicted to occur in spring season where the greatest temperature change (0,6-0,8C°) is expected to occur in summerand autumn season. The changes in total annual precipitation amounts had generally increase tendency (5-25%) over the region especially in winter season30% increase rate was expected over Kırşehir, Aksaray and South part of Kırıkkale province. The changes in total autumn season precipitation amount is predicted to increase (20%) over Niğde but decrease (5%) over the south part of Kırıkkale and southwest part of Kırşehir and Aksaray province in autumn season. Considering the effects of the climate change in the next 30 years, agricultural production in TR71 region is in quite a good place compared to other part of Turkey but this change will indeed affect the agricultural potential of the region substantially. Annual temperature elevation will aggravate the plant temperature stress where increased evaporation will negatively impact the yield, increasing the pressure on the limited irrigation potential. Especially elevated temperature will negatively impact disc development during the seed formation period resulting in yield loss because of the feeble seeds on the disc and the increased disease susceptibility resulting from the cavitation in the inner parts of the disc.